O compromisso ético político do psicólogo terceirizado na política pública de saúde no município de São Paulo - Lima, Luís Carlos de Araújo (2016)
This Doctorate thesis aims at comprehending the effects of the outsourced working place contexts, about the consciousness of the interviewed Psycologists who act in the Public Health Policy of São Paulo City, through the qualitative analysis of significance nucleus extracted from semi-directed interviews. The historical and dialectical method adopted is being developed at the Núcleo de Pesquisa Trabalho e Ação Social (NUTAS) – Research Nucleus of Social Work and Action. The usage of this method intended to cover not only the impacts resulting from historical detail of outsourced management processes, but also to interpret the effects of these processes on the singularities of those interviewed professionals, as off consciousness and alienation/estrangement categories. In order to understand the determiners of the base material, a bibliographical research was held on the structural crisis of the Capitalism which culminated with the decline of Ford/Taylor ways of production and accumulation of wealth that started in the 1960’s, and on the rise of new ways of production/accumulation named by Harvey as “Flexible Capitalism” These new ways of production/accumulation, more adequate to the speculative volatility of the market in a globalized economy, were acclaimed by the consensus in Washington that launched the base to the progress of neoliberal policies. Such policies determined a re-drawing of the States as well as the concept of national sovereign. As a result, the private sector management strategies migrated to social and public policies using the outsourcing as an important management tool. In Brazil, the outsourcing process in public policies was formalized through law number 9.637/98 during Fernando Henrique Cardoso’s government. In São Paulo city, specifically, this process was intensified during both José Serra’s e Gilberto Kassab’s administration, from 2006 to 2012. The main hypothesis of this thesis was that the alienation allowed by outsourced form of administration resulted on competitive strategies of regulation and on the fragmenting of the Public Health Network amongst several social organizations and organizations with the traditional services of a direct administration. These outsourced administration strategies produce a singular form of work organization ruled by the division/dissociation between political environment and work techniques of Psychology. The results of this research have confirmed that the patterns of work organization conceived at the productive sectors of the economy have been migrated to public health policies in São Paulo City through outsourcing, causing not only consciousness alienation of those Psychologists interviewed on the determinant factors of their working conditions, but also the occurrence of uncomfortable relations between outsourced and civil servants professionals. There were also identified resistance processes from these psychologists towards the outsourced strategies management. This resistance was shown through professional values and practices, guided by the SUS principles (Sistema Único de Saúde – Public Health System) as well as the Movement Against Insane Asylum, as a way to keep the sense and meaningfulness of their job, which shall ensure the ethical and political compromise with the profession